Sustainable villages and green landscapes in the 'new urban world'. - (:unkn) unknown (Shaker, 2019)
This book addresses the position of villages and towns in rural areas from the perspective of sustainable development. In the light of world-wide structural urbanisation trends, termed the ‘New Urban World’, we observe an increasing tension between rurality and urbanity, to the extent that the social, economic and political profile of rural areas is significantly weakened or at least under severe stress. In addition to demographic, spatial and socio-economic changes, there is also the threat of a loss of rural sustainability and authenticity caused by pervasive urbanisation in both the developed and the developing world. The volume focuses the attention on sustainable villages and green landscapes in the ‘New Urban World’. It covers a wide range of intriguing questions and issues on modern rurality, written by a pluriform group of international experts. Topics and themes included in this book are: the advantages of sustainable rural development (e.g. nature and agro-tourism, culture), a healthy living climate and a supportive social capital in rural towns and agricultural areas, the economic vitality and innovative survival strategies in these areas, the position of public amenities (e.g. education, retailing) in declining areas, laboratory functions of rurality for new and sound lifestyles, and so forth. This book aims to provide a state-of-art overview and a critical assessment of current trends in rurality and offers also a wide array of policy lessons for sustainable rurality.
Keywords: Ländlicher Raum; Ländliche Gemeinde; Stadt; Dorf; Stadt-Land-Beziehung; Nachhaltige Regionalentwicklung; Nachhaltige Entwicklung; Urbanisierung; Strukturwandel; Nachhaltiger Tourismus; Kulturlandschaft; Ländliche Entwicklung; Soziales Kapital